Studi Penelusuran Alumni Program Studi DIII Adiministrasi Universitas Negeri Surabaya - Prasetyo Isbandono; Weni Rosdiana; Gading Gamaputra; Yuni Lestari; Noviyanti Noviyanti (Department of Public Administration, Universitas Negeri Surabaya, 2022)
This study aims to track alumni and the activities they carry out after graduating from the DIII State Administration Study Program, the State University of Surabaya. The University has made various attempts to find out the careers and activities of its alumni. It is often found that alumni data is not well organized. This research is survey research. The research was conducted with the aim of gathering information about the level of absorption of graduates of the Diploma III Public Administration Study Program in the labour market and feedback on the study program. Based on a survey conducted using the G-form and via Whats App, the responses of D III State Administration alumni to 2015, 2016, 2017 and 2018 batches. Out of a total of 360 alumni, only 62 alumni (17.2%) responded, and they already have steady jobs. Meanwhile, those who are still looking for work or those who have not found work are reluctant to fill out the G-form. Some of them want to continue their studies to the Bachelor level (S1). While the material during college and the ability to adapt to the work environment is enough to contribute to their capabilities in the field of work occupied.